1991
DOI: 10.1017/s002211209100006x
|View full text |Cite
|
Sign up to set email alerts
|

Wave forces on three-dimensional floating bodies with small forward speed

Abstract: A boundary-integral method is developed for computing first-order and mean second-order wave forces on floating bodies with small forward speed in three dimensions. The method is based on applying Green's theorem and linearizing the Green function and velocity potential in the forward speed. The velocity potential on the wetted body surface is then given as the solution of two sets of integral equations with unknowns only on the body. The equations contain no water-line integral, and the free-surface integral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 9 publications
5
48
0
1
Order By: Relevance
“…The resulting Green function is simpler and more efficient compared to the conventional approach (Bessho, 1977). Nossen et al (1991), on the other hand, extended the boundary integral to include the near-field free surface to account for the modification of the steady flow around the body. The use of a Green function that satisfies the free surface boundary condition can lead to the so-called irregular frequencies, at which the matrix equation becomes singular.…”
Section: Potential Flow With Vessel Forward Speedmentioning
confidence: 99%
“…The resulting Green function is simpler and more efficient compared to the conventional approach (Bessho, 1977). Nossen et al (1991), on the other hand, extended the boundary integral to include the near-field free surface to account for the modification of the steady flow around the body. The use of a Green function that satisfies the free surface boundary condition can lead to the so-called irregular frequencies, at which the matrix equation becomes singular.…”
Section: Potential Flow With Vessel Forward Speedmentioning
confidence: 99%
“…Only horizontal components of the steady second order forces will be considered here and the so called far-field expression for these forces is [26]:…”
Section: First Order Loadsmentioning
confidence: 99%
“…Another interesting phenomenon concerning the wave-current-floating body interactions is the secularity (unphysical growth of the solution far away from the body) of the additional perturbation by τ (35). In spite of the recognized secularity of the solution the perturbation by τ is a common approach to treat this problem [26]. Only recently [25,5] it was numerically shown that both solutions (secular and non-secular) are the same as far as the global forces are concerned.…”
mentioning
confidence: 99%
“…The standard potential flow theory assumes that the motion is relatively small and harmonic in time [2,3].…”
Section: Introductionmentioning
confidence: 99%